Role of pyroptosis in diabetic cardiomyopathy: an updated review - Wang, Gan; Ma, Tian-Yi; Huang, Kang; Zhong, Jiang-Hua; Lu, Shi-Juan; Li, Jian-Jun (Frontiers in Endocrinology, 2024)
Diabetic cardiomyopathy (DCM), one of the common complications of diabetes, presents as a specific cardiomyopathy with anomalies in the structure and function of the heart. With the increasing prevalence of diabetes, DCM has a high morbidity and mortality worldwide. Recent studies have found that pyroptosis, as a programmed cell death accompanied by an inflammatory response, exacerbates the growth and genesis of DCM. These studies provide a theoretical basis for exploring the potential treatment of DCM. Therefore, this review aims to summarise the possible mechanisms by which pyroptosis promotes the development of DCM as well as the relevant studies targeting pyroptosis for the possible treatment of DCM, focusing on the molecular mechanisms of NLRP3 inflammasome-mediated pyroptosis, different cellular pyroptosis pathways associated with DCM, the effects of pyroptosis occurring in different cells on DCM, and the relevant drugs targeting NLRP3 inflammasome/pyroptosis for the treatment of DCM. This review might provide a fresh perspective and foundation for the development of therapeutic agents for DCM.